Cross-Validation and Reliability of the Line-Drill Test of Anaerobic Performance in Basketball Players 14-16 Years - Carvalho, Humberto M. (2011)
This study evaluates the validity and reliability of the line-drill (LD) test of anaerobic performance in 76 male basketball players 14.0–16.0 years of age. The Wingate Anaerobic Test (WAnT) was used as the reference for anaerobic performance. Wingate Anaerobic Test and LD test were moderately correlated (0.39 and 0.43, p , 0.01). Estimated age at peak height velocity (APHV) was moderately, negatively, and significantly (p , 0.01) correlated with WAnT peak (r = 20.69) and mean power (r = 20.71); earlier-maturing players had greater anaerobic power. Training experience was not associated with anaerobic performance, but chronological age (CA) and estimated APHV were significant covariates of the LD test (p , 0.05). National players were better than local players on the LD test (p , 0.01) after controlling for CA and body size. Short-term reliability of the LD test (n = 12, 1-week interval) was good: technical error of measurement = 0.44 seconds (95% confidence interval [CI] 0.31–0.75 seconds), intraclass correlation coefficient = 0.91 (95% CI 0.68–0.97), and coefficient of variation = 1.4% (95% CI 1.0–2.3%). Although the relationship between the LD test and WAnT was moderate, the LD test effectively distinguished local- and national-level adolescent basketball players. In contrast to WAnT, the LD test was not influenced by estimated biological maturity status. Thus, the LD test may be suitable for field assessment of anaerobic performance of youth basketball players.